A liberdade em John Stuart Mill na contemporaneidade - Ferreira, Nicholas Gabriel Minotti Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The proposal of this work is manage a thematic study upon the concept of liberty. Such object is too dearly to the philosophy, since it is commonly associated it with norms, conduct patterns, inquiries upon moral and ethical rules, action possibilities, chooses, deliberations and etc. Therefore, to investigate the nature of the liberty, many philosophers has built with their arguments is the way to propel the aspects mentioned above adding with them the social and individual perspectives. This means that the liberty should have rules or limits treated as frontiers (in social perspective) or determinations (individual case) bounded tightly with liberty in relation to a context or particularities of an individual/social action. This kind of interpretation supposes the exam upon liberty in actions that will be or has already been done cutting off the action in a movement of separating it from the individual (and all of its aspects) and analyses carefully that fragment of activity seeking for liberty. This kind of analysis allows, in one hand, an ‘intellectual comfort’ assuring that the individual acted freely or not; in other hand, ignores many fundamental aspects that constitute the liberty. Such aspects can be, for example, the power to change an action which is already in course, customs, opinions and, mainly, fails inherent to the human nature. In this way, this work has as criteria questioning (and why not value) these aspects to observe the nature of liberty in actions within its course and it the meanwhile the arguments to be show here endorses the suspect that the liberty is larger in systems or group of rules that guide the actions. In this way, John Stuart Mill, English philosopher from 19th century, thinks that the individuality would be a fundamental element to the social well-being such as expressed in his book On liberty (1963). The individuality emerges through the opinions expressed in social context. Therefore, when...

A proposta deste trabalho é realizar um estudo temático sobre o conceito de liberdade. O objeto em questão é muito caro para a filosofia, uma vez que é comum associálo com normas, padrões de condutas, investigações sobre regras morais e éticas, possibilidade de ações, escolhas, deliberações e etc. Assim, ao investigar a natureza da liberdade, muitos filósofos construíram argumentações de forma a projetar os aspectos acima mencionados somando-os com os planos sociais e individuais. Isto quer dizer que a liberdade teria regras ou limites referidos como fronteiras (no plano social) ou determinações (no caso individual) vinculados intimamente à liberdade em relação a um contexto ou particularidades de uma ação individual/coletiva. Este tipo de interpretação pressupõe o exame sobre liberdade em ações que serão executadas ou já finalizadas em um movimento de recortar a ação separando-a do indivíduo (e de tudo o que o constitui) e analisa metodicamente aquele fragmento de atividade em busca da liberdade. Esta forma de análise permite, por um lado, um ‘conforto intelectual’ assegurando que um indivíduo agiu livremente ou não; por outro, ignora diversos aspectos fundamentais que constituem a liberdade. Tais aspectos podem ser, por exemplo, o poder de mudar uma ação que já está em curso, costumes, opiniões, e, principalmente, falhas inerentes à natureza humana. Desta maneira, este trabalho tem como critério questionar (e por que não valorizar) estes aspectos com fim a observar a natureza da liberdade nas ações em curso ao passo que a argumentação a ser apresentada reforce a suspeita de que a liberdade é maior que sistemas ou conjunto de regras que orientem as ações. Neste sentido, John Stuart Mill, filósofo inglês do século XIX, pensa que a individualidade seria um elemento fundamental para o bem-estar social tal como expressa em sua...
Keywords: Mill, John Stuart 1806-1873; Liberdade; Filosofia; Philosophy